Aplicação de POAS do tipo O3/UV em integração com material catalítico a base de subproduto de ferro e argilo minerais para a degradação de 2,4 e 2,6-dinitrotolueno em água vermelha - Walter, Jilvana Barbara (2021)
Zero valence iron is an abundant and easily obtainable element, especially on a micrometric scale, and it can present high reactivity and significant potential to be used in advanced oxidative processes (POA's) as a catalytic material. POA's are considered emerging processes, capable of mineralizing or degrading chemical contaminants under optimized conditions. In this work, the application of advanced oxidative processes of the O3/UV type (photo-ozonization) in sequential integration with catalytic material based on metallic iron slag (SZVI) in micrometric scale and mineral matrix, for the treatment of an industrial effluent was studied. from the explosives industry contaminated with nitroaromatic compounds. Two types of mineral matrix composition were studied (SZVI+kaolinite and SZVI+powder pumice stone), with total degradation of both 2,4 and 2,6-dinitrotoluene and removal of residual ozone, with an effective contribution from the catalytic matrix. In the physical characterization, performed through X-Ray Diffractometry (XRD) in a sample of catalytic matrix before and after use in the treatment of industrial red water effluent, although head losses by leaching measured by the reduction of the intensity of typical crystalline phases were observed of zero valence iron, maintenance of crystallinity was observed, suggesting potential reuse of the catalytic material.